LITERATURE REVIEW OF FINANCIAL PERFORMANCE AND FINANCIAL DISTRESS: LIQUIDITY AND PROFITABILITY ANALYSIS (FINANCIAL MANAGEMENT LITERATURE REVIEW) - Sukenti (Dinasti International Journal of Digital Business Management, 2022)
Literature article Reviewing the Effect of Liquidity and Profitability in the context of financial management, a scientific study titled Financial Performance and Financial Distress tries to provide a research hypothesis on the interaction between factors. This literature review was written using the library research approach, including information from online academic databases like Google Scholar, Mendeley, and others. The outcomes of this article's literature review are:1) Liquidity affects Financial Performance; 2) Profitability has an effect on Financial Performance; 3) Liquidity affects Financial Distress; 4) Profitability has an effect on Financial Distress; and 5) Financial Performance Affects Financial Distress; In addition to these 2 external factors that influence the endogenous variables Financial Performance and Financial Distress there are still other additional elements, like as Leverage, Solvency and Activity variables.